Cannabis-induced cardiac arrhythmias: mechanistic insights, epidemiologic patterns, and clinical implications - Shukla, Pranav Sanjay; Desai, Twaraa; Gupta, Aditya; Sharma, Nishant; Abedin, Zainul (International Journal of Research in Medical Sciences, 2025)
As legalization and therapeutic interest expand, the global use of cannabis has significantly increased. Nonetheless, its cardiovascular impacts-particularly the risk of heart arrhythmias-are still not well acknowledged. Recent findings suggest that cannabis, especially its psychoactive element Δ9-tetrahydrocannabinol (THC), could have a mechanistic influence in triggering both atrial and ventricular dysrhythmias. A narrative review was performed utilizing pertinent literature released from January 2000 to May 2024. Databases explored encompassed PubMed, Scopus, and Web of Science. Studies were chosen for their relevance to cannabis-related arrhythmias, encompassing experimental, observational, and clinical findings. Focus was directed towards mechanistic understanding, epidemiological patterns, and clinical results. Cannabis use has been linked to a range of arrhythmias, from harmless palpitations to severe ventricular tachyarrhythmias and sudden cardiac arrest. THC affects cardiomyocyte ion channels, extends repolarization, and modifies autonomic control, establishing a basis for arrhythmogenesis. Long-term exposure could lead to myocardial fibrosis and oxidative stress. Increased risk is observed in young adults, regular users, and those with psychiatric or pre-existing heart issues. Even with these results, awareness and screening continue to be restricted in regular clinical practice. Cannabis presents a clinically important yet overlooked danger for cardiac arrhythmias. Healthcare professionals ought to take into account recent cannabis consumption in patients who show unexplained arrhythmias. There is a critical requirement for longitudinal research and revised clinical guidelines to guide risk evaluation, patient education, and monitoring approaches.